Developing Authentic Assessment Rubric for EFL Teachers on 6th Grade of Elementary School - Kadek Dwi Candra Oktariana (Universitas Islam Lamongan, 2022)
ABSTRACT21st century learning have a further demand rather than previous learning. Other than acquiring knowledge, students also have to use their knowledge and apply it into the real life situation. The process of applying knowledge that have learnt are important in order to activate students’ authentic skill which are highly needed in today’s era. During the process of applying it, students are hoped to use their critical thinking, collaboration and creativity too. One thing that teachers can do to improve the quality of education is by implementing assessment in the classroom. The use of assessment make teachers able to collect a lot information from students as well as how good a certain method of learning to be applied in the classroom. This information will be collected and use to make a right decision in the learning process. Authentic assessment allowed both teachers and students know their learning progress. They will know how far they have understood the material since they have to remember the material and practice it through several task based on real-life situation. By using authentic assessment it makes students possible to perform related skill which are needed in real life. Those skill are 4C skill which already explained in the 21st century which are communication, creativity, critical thinking, and collaboration